Enhancement of Thermoelectric Properties of PEDOT:PSS and Tellurium-PEDOT:PSS Hybrid Composites by Simple Chemical Treatment - Jin Bae, Eun (Sci Rep, 2016)
The thermoelectric properties of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) and tellurium-PEDOT:PSS (Te-PEDOT:PSS) hybrid composites were enhanced via simple chemical treatment. The performance of thermoelectric materials is determined by their electrical conductivity, thermal conductivity, and Seebeck coefficient. Significant enhancement of the electrical conductivity of PEDOT:PSS and Te-PEDOT:PSS hybrid composites from 787.99 and 11.01 to 4839.92 and 334.68 S cm(−1), respectively was achieved by simple chemical treatment with H(2)SO(4). The power factor of the developed materials could be effectively tuned over a very wide range depending on the concentration of the H(2)SO(4) solution used in the chemical treatment. The power factors of the developed thermoelectric materials were optimized to 51.85 and 284 μW m(−1) K(−2), respectively, which represent an increase of four orders of magnitude relative to the corresponding parameters of the untreated thermoelectric materials. Using the Te-PEDOT:PSS hybrid composites, a flexible thermoelectric generator that could be embedded in textiles was fabricated by a printing process. This thermoelectric array generates a thermoelectric voltage of 2 mV using human body heat.